Window of opportunity in axial spondyloarthritis: A Stitch in Time - Parasar Ghosh; Pradip Kumar Sarma; Padmanabha Shenoy; Dhrubojyoti Mukherjee; Akshay Desai (International Journal of Medical Research and Review, 2022)
Axial spondyloarthritis comprising both non-radiographic axial spondyloarthritis and ankylosingspondylitis has a deleterious impact on the patient’s quality of life with a detrimental outcome ofstructural damage. Although in the current era of diagnostic advancements, axSpA can be diagnosedearly within a short period after the onset of symptoms, but still there is a delay of up to severalyears in many parts of the world. The concept of a window of opportunity is primarily derived fromrheumatoid arthritis, which is relevant in the context of axSpA based upon the early diagnosis and tocommence highly effective treatment with biologics like anti-TNF and anti-IL-17 to modify thedisease process for arresting structural damage or syndesmophytes formation. Still, challenges existfor early diagnosis of SpA in patients with low back pain which ultimately creates a barrier toeffective treatment initiation. More robust researches along with the available evidence on both theaspects of clinical and imaging factors are the way forward for the early identification of susceptibleindividuals for early intervention with a better outcome.